The effect of fire on ant assemblages does not depend on habitat openness but does select for large, gracile predators - Tom R. Bishop; Andy Tomlinson; Travers McNeice; Spyros Sfenthourakis; Catherine L. Parr (Ecosphere, 2021)
Abstract Ecosystems can respond in a variety of ways to the same agent of disturbance. In some contexts, fire causes large and long‐lasting changes to ecological communities. In others, fire has a limited or short‐lived impact on assemblages of animals and plants. Understanding why this occurs is critical if we are to manage these kinds of disturbances across the globe. A recent synthesis proposed that these seemingly idiosyncratic responses to fire can be understood in the context of habitat openness pre‐disturbance. Assemblages in open habitats should respond less to a single fire event that those in closed habitats. We provide a test of this hypothesis by examining the response of ant (Hymenoptera: Formicidae) communities to large‐scale fire events in three habitats of different natural canopy openness on the Peloponnese peninsula in Greece. We also test the hypothesis that assemblage responses to fire are trait dependent. Fire simplifies the physical structure of the environment, increases insolation, and limits opportunities for ants to exploit herbivorous feeding strategies. Consequently, we predict that ants will face a strong environmental filter between unburnt and recently burnt plots, which will be reflected in their functional morphology. Our analysis shows that burnt plots have more individual ants, more species and an almost complete compositional change relative to unburnt plots. These changes do not depend on initial canopy openness. Rather, we suggest that openness must be interpreted relative to the study taxon; for ants, openness should be measured closer to the ground level. In our study, ground‐level openness does not vary across the plots, which may explain the results. Furthermore, ants in burnt plots are significantly larger, have relatively longer legs, relatively longer mandibles, and more elongate heads. This morphotype fits with our prediction of ants that can move and feed successfully in the burnt micro‐landscape. Ultimately, more work is needed to fully explore the relationship between habitat openness and the response to fire. Our results showing a filtered set of ant morphologies in burnt environments suggest that ant traits may offer a further way forward to understand the faunal response to fire and disturbance in general.